2009
DOI: 10.2754/avb200978010029
|View full text |Cite
|
Sign up to set email alerts
|

Microelement Supplementation in Dairy Cows by Mineral Lick

Abstract: The aim of this experiment was to verify the option of providing microelement supplementation to dairy cows in the dry period through supplemented mineral lick, and then to compare the content of microelements in the blood, colostrum and milk. The experiment was carried out on a farm with Czech Fleckvieh dairy cows. We formed an experimental group (E), supplied with mineral lick ad libitum enhanced with organic forms of microelements (Se, Zn, Cu, Mn) for four to five weeks before parturition and 1 week after p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…and for this reason they are added to feeds in various organic as well as inorganic forms (Pechova et al, 2008Krys et al 2009;Mala et al, 2009;Misurova et al, 2009a).…”
mentioning
confidence: 99%
“…and for this reason they are added to feeds in various organic as well as inorganic forms (Pechova et al, 2008Krys et al 2009;Mala et al, 2009;Misurova et al, 2009a).…”
mentioning
confidence: 99%
“…A lack of differences is likely due to milk samplings occurring after treatment termination. Source of Cu, Zn, and Mn during late gestation did not affect mineral composition of milk in beef ( Harvey et al, 2021a ) or dairy cows ( Krys et al, 2009 ). Supplementing dairy cows with different sources of trace minerals during late gestation and lactation has resulted in variable milk macronutrient yield differences ( Osorio et al, 2016 ), but generally no effects are observed even when mineral supplementation treatments continue into lactation ( Yasui et al, 2014 ; Roshanzamir et al, 2020 ; Mion et al, 2022 ).…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, the experiment of Cu and Mn supplementation, indicated that high doses of Mn inhibits Cu activity and consequently may causes Fe deficiency illnesses. The prevention of minerals deficiencies in adult cows diet is usually conducted by using mineral licks (Krys et al, 2009). …”
Section: Resultsmentioning
confidence: 99%